Strengthening integrated learning: Towards a new era for pluriliteracies and intercultural learning - Do Coyle (Universidad de La Sabana, 2015)
Over the last two decades, the expansion of Content and Language Integrated Learning (CLIL) on a global scale has brought to the fore challenges of how alternative, more holistic approaches to learning might transform classrooms into language-rich transcultural environments. Integrated approaches have the potential to offer learners the opportunity to engage in meaning-making and language progression through cognitively challenging and culturally-embedded sequenced activities, which are reflected in the 4Cs Framework (Content, Cognition, Communication, and Culture). However, the 4Cs also present many challenges-it is well documented that the potential of CLIL is difficult to realise due to the impact of complex contextual variables. The importance of classroom language is emphasised, as is the need for learners to access different kinds of language to enable them to learn effectively using a language which is not their first-as represented in the Triptych. Whilst the 4Cs bring together the components of CLIL, research by the Graz Group into how these might be integrated has led to the development of the Pluriliteracies Framework. The core of the Pluriliteracies model lies in the space where conceptualizing and communicating come together. Here learners are encouraged to language (or articulate) their learning in their own words. For this to happen, new ways of conceptualizing, planning, and sequencing activities that support learners in accessing new knowledge whilst developing existing and new language skills have to be shared and understood by teachers. The Pluriliteracies model is evolving, and there is a clearly a need for further work.